2019
DOI: 10.3390/polym11081288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reinforcement Structures and Hybrid Types on Inter-Laminar Shear Performance of Carbon-Glass Hybrid Fibers/Bismaleimide Composites under Long-Term Thermo-Oxidative Aging

Abstract: The effects of reinforcement structures and hybrid types on the inter-laminar shear strength (ILSS) of carbon-glass hybrid fibers/bismaleimide composites under thermo-oxidative aging conditions were investigated. The process resulted in progressive deterioration of the matrix and fiber/matrix interfaces, in the form of chain scissions, weight loss, and fiber/matrix debonding, which significantly led to the decrease of the ILSS of composites. Moreover, the three-dimensional orthogonal woven hybrid composites (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Bin Yang et al [15] reported that the combination of CF and GF in epoxy resin enhanced the mechanical performance of the resulting composites at high temperatures. Our previous study [16] also confirmed that the CF/BMI interfacial bonding was stronger than GF/BMI at the same TOA condition. Thus, understanding the effect of TOA on the performance of hybrid composites has become vital for the effective design of hybrid composite materials.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…Bin Yang et al [15] reported that the combination of CF and GF in epoxy resin enhanced the mechanical performance of the resulting composites at high temperatures. Our previous study [16] also confirmed that the CF/BMI interfacial bonding was stronger than GF/BMI at the same TOA condition. Thus, understanding the effect of TOA on the performance of hybrid composites has become vital for the effective design of hybrid composite materials.…”
Section: Introductionsupporting
confidence: 74%
“…On increasing the aging time, map cracking can be observed in Figure 6(c) and (d). The observed phenomenon can be attributed to the severe degradation of the resin, revealed in our previous study [16]. Owing to the breaking of the chains in BMI resin, the resulting shrinkage and mass loss induce the initiation of small cracks.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…When the material receives impact, the cross-linked network structure will tend to help the resin matrix to bear the external force and conduct the force to the GO through the molecular chain, so as to achieve the purpose of toughening the resin matrix [ 38 , 39 ]. Recently, there has been more focus on incorporation of GO into BMI networks [ 40 , 41 , 42 , 43 , 44 , 45 ]. However, scarce literature focused on improving toughness while improving thermomechanical properties has been reported.…”
Section: Introductionmentioning
confidence: 99%